Impacts and consequences of fad diets and supplementation on eating behavior (Research, Society and Development, 2021)
Fad diets are gaining more and more evidence in the media and social networks being treated as “miracle diets” promising immediate results for aesthetic purposes in a short period. The objective of this work is to discuss the impacts and consequences of restrictive diets and supplements that are used without the prescription of a qualified professional. This work is a bibliographic review, where the following databases were accessed: Pubmed, Academic Google and SciELO. The selected articles were mostly after 2010, but it was necessary to search for research carried out before 2010, due to the absence of a concrete database. The importance of proper guidance from a professional nutritionist in relation to a patient's eating plan is essential to avoid damage to mental and physical health caused by dietary restrictions. Also noteworthy is the correct use of dietary supplements prescribed by a professional nutritionist and the individuality of each one for the body of each patient, thus avoiding harming health with incorrect use.